2018
DOI: 10.1534/g3.117.300341
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Heterochromatin Domains on Replication Factors

Abstract: Chromatin structure regulates both genome expression and dynamics in eukaryotes, where large heterochromatic regions are epigenetically silenced through the methylation of histone H3K9, histone deacetylation, and the assembly of repressive complexes. Previous genetic screens with the fission yeast Schizosaccharomyces pombe have led to the identification of key enzymatic activities and structural constituents of heterochromatin. We report here on additional factors discovered by screening a library of deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 97 publications
5
28
0
Order By: Relevance
“…This might be relevant to the mode of action of IR-R as IR-R possesses ars activity on plasmids (1) and exerts a control on DNA replication in the chromosome (39), suggesting the boundaries might couple DNA and chromatin replication. This is also suggested by the spectrum of mutations affecting heterochromatic silencing at (EcoRV)::ade6 + that define many replication factors (40).…”
Section: Discussionmentioning
confidence: 90%
“…This might be relevant to the mode of action of IR-R as IR-R possesses ars activity on plasmids (1) and exerts a control on DNA replication in the chromosome (39), suggesting the boundaries might couple DNA and chromatin replication. This is also suggested by the spectrum of mutations affecting heterochromatic silencing at (EcoRV)::ade6 + that define many replication factors (40).…”
Section: Discussionmentioning
confidence: 90%
“…Among the newly identified factors, six subunits of Set1C and Brl2 are connected to Class Ib factors. While Pof3, Ckb1 and Elp6 show no direct interaction with Class Ib factors in the STRING analysis ( Fig 6A ), several studies have reported that Pof3 plays a role in heterochromatin silencing [ 70 72 ] and Ckb1 phosphorylates Swi6 [ 68 ]. Elp6 is an orthologue of a part of the six-subunit Elongator complex (Elp1-6) in S .…”
Section: Resultsmentioning
confidence: 99%
“…However, rather than participating in imprint formation, we found that Pof3 affects donor selection. Pof3 is also required for heterochromatic silencing near mat3 [ 70 ]. We speculate that both effects are brought about by the Pof3-mediated degradation of replisome components [ 80 ] or of Ams2, a cell cycle-regulated transcription factor for histone genes [ 81 ] that also mediates long range chromosomal interactions [ 82 ] and interacts with Raf1, a component of CLRC [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…One such HDACs recruited to this region is Snf2/Hdac Repressive Complex, which unloads the RNA Pol II from the repeats to halt transcription and prevents the replication fork from stalling. More recently, additional factors, ranging from ubiquitin ligases (Pof3, Def1), proline cis–trans isomerases (Fkbp39), chromatin remodeler (Fft3), and cohesion release factors (Wpl1), have been shown to be involved in this process . In the absence of cotranscriptional RNAi, stalled replication forks are repaired without histone modifications, by homologous recombination .…”
Section: Heterochromatic Transcripts In Regulating Replicationmentioning
confidence: 99%
“…One such HDACs recruited to this region is Snf2/Hdac Repressive Complex, which unloads the RNA Pol II from the repeats to halt transcription and prevents the replication fork from stalling. More recently, additional factors, ranging from ubiquitin ligases (Pof3, Def1), proline cistrans isomerases (Fkbp39), chromatin remodeler (Fft3), and cohesion release factors (Wpl1), have been shown to be involved in this process [50]. In the absence of cotranscriptional RNAi, stalled replication Sir2 and HP1 in the absence of RNAi deacetylases H3K9 and H3K4 residues and reduces histone turnover to promote silencing Nascent CTs fold to double-stranded hairpin structure that is acted upon by Dcr1-dependent processing of siRNA [22,23] S. pombe dh/dg repeats Mlo3-Trf4/Air2/Mtpr4p polyadenylation complex RNA surveillance complex is sufficient to bypass the RNAi pathway to trigger heterochromatin assembly [24] S. pombe Primal RNA (priRNA) DCR-independent class of small RNAs are generated by Argonaute and Triman (3'-5' exonuclease) and targeted via exosomes at the developmental genes [25] Drosophila melanogaster priRNA/ endo siRNA Mutation in AGO2 or piwi increased silencing at piRNA clusters and HP1 association, suggesting heterochromatin formation also occurs independently of endo-siRNA/piRNA pathways [26] forks are repaired without histone modifications, by homologous recombination [48].…”
Section: Heterochromatic Transcripts In Regulating Replicationmentioning
confidence: 99%